2013
DOI: 10.1007/s10522-013-9475-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondria in age-related hearing loss

Abstract: Age-related hearing loss (ARHL), the hearing loss associated with aging, is a vital problem in present society. The severity of hearing loss is possibly associated with the degeneration of cochlear cells. Mitochondria play a key role in the energy supply, cellular redox homeostasis, signaling, and regulation of programmed cell death. In this review, we focus on the central role of mitochondria in ARHL. The mitochondrial redox imbalance and mitochondrial DNA mutation might collaboratively involve in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…The incidence and frequency of mtDNA point mutations and deletions increase exponentially with age and contribute to cellular senescence in humans, monkeys, and rodents, thus providing a causative link between mtDNA mutations and aging phenotypes in mammals [71]. In the cochlea, it has been hypothesized that the cochlear mitochondrial redox imbalance and mitochondrial DNA mutation and deletion might be collaboratively involved in ARHL [72]. One specific mitochondrial common deletion (mtDNA4977) is frequently observed in the temporal bone of patients with ARHL, and its measured levels are strongly correlated with the severity of ARHL [73].…”
Section: Mitochondrial Dna Mutations and Dysfunctionmentioning
confidence: 99%
“…The incidence and frequency of mtDNA point mutations and deletions increase exponentially with age and contribute to cellular senescence in humans, monkeys, and rodents, thus providing a causative link between mtDNA mutations and aging phenotypes in mammals [71]. In the cochlea, it has been hypothesized that the cochlear mitochondrial redox imbalance and mitochondrial DNA mutation and deletion might be collaboratively involved in ARHL [72]. One specific mitochondrial common deletion (mtDNA4977) is frequently observed in the temporal bone of patients with ARHL, and its measured levels are strongly correlated with the severity of ARHL [73].…”
Section: Mitochondrial Dna Mutations and Dysfunctionmentioning
confidence: 99%
“…[ 5 , 6 ]. As for Sod1 , it has been reported that as the amount of oxidative stress in the cells of the auditory organ increases, the amount of Sod1 also increases [ 7 , 8 ]. In addition, numerous reports have suggested that in these models, abnormal potassium channels resulting from mass transfer errors cause cell death [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presbycusis is defined as the progressive decline of hearing ability during aging and causes symmetrical, bilateral, high-frequency sensorineural hearing impairment 3. As a multifactorial disorder, presbycusis is associated with a combination of environmental factors, medical history, and nuclear and mitochondrial genome variation 46. Presbycusis has a great impact on the quality of life of patients as it impairs communication skills and independent daily activity and, therefore, gradually diminishes psychosocial functioning 7.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are considered one of the main factors in the progression of presbycusis;4 these organelles are responsible for vital cellular functions, including energy production, apoptosis, cell signaling, and calcium storage. Variants in the mtDNA control region are associated with different disorders, including cancer, Huntington disease, and β-thalassemia 1012.…”
Section: Introductionmentioning
confidence: 99%